The use of Facebook as Useful Tool for Facilitating Communications Between Teachers and Students / ประสิทธิภาพการใช้ Facebook เพื่อเป็นเครื่องมือในการติดต่อสื่อสาร ระหว่างอาจารย์ผู้สอนและนิสิต - จีราวรรณ ทองลิ้ม, Jeerawan Thonglim / (Journal of Community Development Research (Humanities and Social Sciences), 2015)
งานวิจัยนี้มีวัตถุประสงค์เพื่อแก้ปัญหาในการติดต่อสื่อสารระหว่างอาจารย์และนิสิตโดยใช้ Facebook เป็นเครื่องมือในการติดต่อสื่อสารระหว่างอาจารย์ผู้สอนและนิสิต กรณีศึกษาในรายวิชา ชีวเคมี (411221) ของภาควิชาชีวเคมี คณะวิทยาศาสตร์การแพทย์ ด้วยการติดต่อสื่อสารระหว่างอาจารย์ผู้สอนและนิสิตผู้เรียน ในรายวิชามีเวลาที่จำกัดในการสอนและมีโอกาสน้อยในการพบปะนิสิตแต่ละสาขานอกชั่วโมงเรียน ส่งผลให้นิสิตอาจไม่ได้ทราบข้อมูลอย่างทั่วถึง เช่น การประกาศแจ้งการเปลี่ยนแปลงการเรียนการสอน โดยเฉพาะในกรณีมีการเปลี่ยนแปลงอย่างเร่งด่วน การชี้แจงรายละเอียดเกี่ยวกับเนื้อหาที่จะใช้เรียน การแจ้งการรับ-ส่งเอกสารประกอบการเรียนการสอน การแจ้งผลสอบ หรือการตอบข้อซักถามต่างๆ ของนิสิต ซึ่งการติดต่อสื่อสารที่ใช้ส่วนใหญ่จะเป็นการติดต่อสื่อสารผ่านทางตัวนิสิตเอง หรือผ่านทางตัวแทนนิสิต หรือการแจ้งประกาศผลทางบอร์ดของภาควิชา/คณะ ซึ่งแนวทางดังกล่าวอาจจะไม่เพียงพอและไม่สอดคล้องกับวิถีในปัจจุบัน จะพบว่า Facebook เป็นโซเชียลเน็ตเวิร์คที่ได้รับความนิยม จะเห็นได้ว่า ตอนนี้ได้ถูกใช้ในการสื่อสารทางสังคม เป็นเครื่องมือเครือข่ายสังคมที่มีอยู่บนอินเทอร์เน็ต โดยส่วนใหญ่ พบว่า ทุกคนมีบัญชีรายชื่อของ Facebook เกือบจะ 100% ของคนหนุ่มสาว โดยเฉพาะอย่างยิ่งในนักศึกษามหาวิทยาลัย ดังนั้น Facebook จึงได้ถูกพิจารณาให้เป็นเครื่องมือที่ใช้ในการแก้ปัญหาของการสื่อสารระหว่างอาจารย์และนิสิต ในการสื่อสารที่มีประสิทธิภาพและใช้งานง่ายเป็นการส่งเสริมการสื่อสารที่ดี งานวิจัยนี้ได้เริ่มในภาคการศึกษาที่ 1 ปีการศึกษา 2557 ด้วยการสร้าง Fanpage Facebook ของรายวิชา เพื่อใช้เป็นช่องทางในการสื่อสารระหว่างอาจารย์และนิสิต รวมถึงการเพิ่มเอกสารประกอบการสอน  สไลด์ Powerpoint หรือ eBook ต่างๆ เช่นเดียวกับการประกาศข่าวประชามสัมพันธ์ที่แก่นิสิต ซึ่งนิสิตสามารถสื่อสารโต้ตอบกับอาจารย์ได้เฉพาะเจาะจง ดังนั้น จึงเป็นการอำนวยความสะดวกสบายและเป็นการสื่อสารแบบสองทาง ในตอนท้ายของการวิจัยได้จัดทำแบบสอบถามความพึงพอใจของนิสิตต่อการใช้ Facebook เป็นเครื่องมือในการติดต่อสื่อสารระหว่างอาจารย์และนิสิตมนรายวิชา โดยผลจากแบบสอบถาม ที่ได้อยู่ในระดับสูงของความพึงพอใจที่มีต่อการใช้ Facebook ในสถานการณ์เช่นนี้เห็นได้ชัดว่า ประสบความสำเร็จมากและเป็นประโยชน์ ตรงตามวัตถุประสงค์ เพื่อความสะดวกในการสื่อสารระหว่างอาจารย์และนิสิต   คำสำคัญ : เครือข่ายสังคมออนไลน์  เว็บไซต์เฟสบุ๊ค   Abstract The objective of this research was to study the use of Facebook as a useful tool for facilitating communications between teachers and students. Facebook was chosen given its prominent role in contemporary social interaction by the Internet. A case study approach was used, involving the students and staff in the Biochemistry course (411221) offered by the Department of Biochemistry in the Faculty of Medical Sciences. Communication between teachers and the students in their classes, and with graduate students, are limited given the restricted time available to teach and for interaction between teacher and student. Teachers need to provide students with information, both administrative and academic, and students need to have easy access to that information, some of which may be announcements of changes to teaching times, class locations etc. where it is urgent to send, and receive, that information. Other administrative information, such as exam result notification is essential, and there is a significant amount of teaching and learning material that needs to be communicated; subject curriculum information, responses to student requests for assistance in understanding subject matter, ready availability of Guidelines and Policies. All must be conveniently available, sent, received or accessed. Facebook is now seen as almost an imperative in contemporary social communication. It is the predominant social networking tool available on the Internet. It is used by the vast majority, approaching 100%, of especially young people today, which obviously includes university students. It was therefore considered to be the best social networking tool to be considered in solving the problems of communication between teachers and students, and enabling efficient, effective and easy communication, as well as encouraging better communication.  This research was commenced in Semester 1 of the 2557 academic year and continued into the second semester. A Facebook ‘fan page’ was established, and used as the primary communication medium. All appropriate administrative and academic documentation for the course, in the Faculty was published on this web page. This included curriculum documents, lecture notes, video clips, Powerpoint slides and a digital e-book, as well as announcements of interest to students. Students were able to send messages and documents to specific teachers, thereby creating a convenient, two-way communication facility. At the end of each term a Satisfaction Questionnaire was completed by the students and teachers. This was a paper based questionnaire done in the classroom. Analysis of the questionnaire indicated a high level of satisfaction with the concept and actual use of the Facebook page. The use of Facebook in this situation was evidently very successful and beneficial in its objectives and outcomes; to facilitate communications between teachers and students.   Keywords: Social Networks, Facebook Website
Keywords: เครือข่ายสังคมออนไลน์ เว็บไซต์เฟสบุ๊ค Social Networks, Facebook Website